Instructional effects on critical thinking: Performance on ill-defined issues - Angeli, Charoula; Valanides, Nicos (Learning and instruction, 2009)
Undergraduate students in dyads ( N = 72) were randomly and equally assigned to four groups, namely three teaching groups (General, Infusion, and Immersion) and the control group. Students were initially administered the California Critical Thinking Skills Test (CCTST). After instruction, each dyad's critical-thinking performance on an ill-defined problem was tested. A one-way ANCOVA, with the mean CCTST score of each dyad as covariate, indicated that the covariate and the teaching method were significant. Post hoc comparisons showed that the Infusion and the Immersion groups outperformed only the control group. Other quantitative and qualitative analyses revealed that students assigned to the different teaching groups exhibited diverse understandings of critical thinking.